The German girl [compact disc, unabridged] - Correa, Armando Lucas, 1959- (Simon & Schuster Audio, 2016)
In 1939 before everything changed, Hannah Rosenthal lived a charmed life. Her family moved in Berlin's highest social circles, admired by friends and neighbors. She spent her afternoons at the park with her best friend Leo Martin. But, in an instant, that sunlit world vanished. Now the streets of Berlin are draped with red, white, and black flags; their fine possessions are hauled away, and they are no longer welcome in the places that once felt like home. The two friends make a pact: come what may, they promise to have a future together. Decades later in New York City on her eleventh birthday, Anna Rosen receives a mysterious envelope from Hannah, a great-aunt she has never met but who raised her deceased father. Anna and her mother travel to Havana to meet Hannah, who is turning eighty-seven years old. Hannah reveals old family ties, recounts her journey aboard the Saint Louis and, for the first time, reveals what happened to her father and Leo.